Das kalabrische Erdbeben von 1783 als "spettacolo delle rivoluzioni": Francesco Saverio Salfis "Saggio di fenomeni antropologici relativi al tremuoto" - Winkler, Daniel (Annali di Ca' Foscari. Serie orientale, 2019)
This contribution will focus on Francesco Saverio Salfi’s treatise - Essay on Anthropological Phenomena in Relation to the Earthquake - (1787). In his text, Salfi focuses on analysing the rise of superstition and bigotry in Calabria after the Earthquake of 1783, but also develops anthropological and philosophical considerations on the phenomenon of the earthquake. His metaphorically dense text revolves around the semantic fields of trembling and disaster, revolution and spectacle. Through intertextual, especially theatrical techniques, this article will argue the text to become an emblem for the necessity of a ‘revolutionary’ change in respect to the affective, social, and ethic Status Quo in Calabria and beyond.
Gesehen am 21.12.2021